(untitled) (Colloquia Comparativa Litterarum, 2025)
The poetry school of Thessaloniki, considered as a simple trend by the modern Greek critics, influenced significantly the reception of modernism by the modern Greek literature. The Greek translations of modernist writers, mostly prose writers (V. Woolf, M. Proust, J. Joyce), appeared in the literature reviews of Thessaloniki. Few studies have focused on the field of poetry, where the work of F. G. Lorca had a major impact on various poetic tendencies defined by the left-wing or idealist poets of Thessaloniki. This article aims to study the influence on the poetic existence of certain of poets of Thessaloniki.